Arquitetura neoclássica e cotidiano social do centro histórico de Fortaleza: da Belle Époque ao ocaso do início do século XXI - Antonio Gilberto Abreu de Souza (2012)
This thesis deals with the Neoclassic architecture and everyday social of the Historical Center of Fortaleza - of the Belle Époque to decline of the beginning of the XXI century. It is a study about the evolution spatial and architectural neighborhood Center in Fortaleza, an area with deep historical heritage and that has been wearing progressively. The general objective of this thesis is a study that can identify and analyze, taking as reference the Neoclassical architecture, the main actors, problems and potential, in the period that covers the end of the nineteenth century to today, about the evolution spatial, social and cultural of the Historic Center of Fortaleza. It has specific objectives are the analysis of the history of the use of the soil of the neighborhood, the research of the landmarks of cultural identity and architectural, the influence of Neoclassicism and the Belle Époque and the factors that resulted in its decline. The methodology used for these goals revolves around, qualitatively, around the textual review in works and documents, the questioning of some social agents involved through field research and analysis of architectural heritage Neoclassical and Eclectic. The study, to check the current trend of transformation in the neighborhood Centro as a place of memory, and the possible effects of physical interventions on the conservation and revitalization of the set built in the region, seeks to develop arguments contributory to the expansion of discussions about the changes to which the neighborhood needs.